Hybrid composites manufactured by resin infusion with a fully recyclable bioepoxy resin. (1st January 2018) - Cicala, G.; Pergolizzi, E.; Piscopo, F.; Carbone, D.; Recca, G.
Abstract: Bioepoxy based monomers were formulated with a cure inhibitor and a cleavable amine to obtain a recyclable epoxy system suitable for resin infusion at room temperature. Hybrid flax/carbon fiber layup were used. Tensile, flexural and dynamo-mechanical properties for the composites were studied. The cured laminates were chemically recycled obtaining from the epoxy matrix a thermoplastic. The recycled was processed by fused deposition modelling (FDM) and injection molding after mixing with short kenaf fibers.